SYMBOLIC AND NARRATIVE FUNCTION OF PHYTONYMS IN ALAIN-FOURNIER’S NOVEL LE GRAND MEAULNES - Bobokalonov Odilshoh Ostonovich; Rahimova Markhabo Rahmon qizi; Qosimova Umeda Qurbon qizi (Bright Mind Publishing, 2025)
This article explores the symbolic and narrative functions of phytonyms, plant-related lexical items in Alain-Fournier’s novel Le Grand Meaulnes. Through a linguistically oriented textual analysis, the study demonstrates how botanical terms contribute to the construction of atmosphere, emotional expression, and thematic coherence in the novel. Drawing from both literal and figurative instances, the analysis reveals that phytonyms serve as key narrative devices that reflect the protagonist’s emotional development and reinforce the novel’s central motifs of nostalgia, lost innocence, and romantic idealism. The use of phytonyms is also examined in relation to French idiomatic expressions, metaphorical traditions, and cultural symbolism, illustrating how natural elements are integrated into the semantic and stylistic fabric of the text. Furthermore, a brief comparative note with Uzbek cultural symbolism highlights how the connotative value of plant names can vary across linguistic and cultural systems. Overall, the study argues that phytonyms in Le Grand Meaulnes function not only as descriptive tools but as deeply meaningful symbols within a wider narrative ecology.
Keywords: Phytonym, phytonymy, French literature, Alain-Fournier, Le Grand Meaulnes, Symbolism, narrative linguistics, cultural semantics, lexical analysis, figurative language, literary ecology, cross-cultural comparison, adolescent identity, shifonema.